Pemberdayaan Pemandu Wisata Dalam Mengembangkan Rute Walking Tour Baru di Kota Pusaka Lasem - Wulandari, Prisca Kiki; Sembiring, Ruth Agnesia; Balina, Bela; Vernanda, Shinta Ayu; Wibowo, Syaharani; Mufti, Muhammad 'Afwan; Fadilla, Firza Azzam (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to improve the capacity of local tour guides in the Lasem Heritage City area, Rembang Regency, Central Java. The main problem faced by the tour guide community in Lasem is the lack of official and standardized guides that can be used as a common reference in conveying information to tourists. This has an impact on inconsistencies in the delivery of historical and cultural narratives, as well as reducing the quality of the tourism experience. In addition, some guides also still need to improve their communication skills, interesting guiding techniques, and digital media-based promotional strategies. In response to these needs, this community service activity was carried out through a series of collaborative processes between academics and the local community, starting from compiling the content of the “Jelajah Kota Pusaka Lasem” guidebook, training in delivering history-based narratives, to strengthening promotional skills and the use of social media. This activity also involved the cultural community and active guides in the process of compiling materials, validating content with local historians, and conducting guide simulations as a means of practice. This activity uses the Participatory Action Research (PAR) method which places the community as the main subject. The results of this program showed that the mentoring activity succeeded in increasing the understanding, confidence, and quality of narrative delivery by tour guides. The guidebook that was compiled has become a common reference that strengthens the consistency of information and the tourist attraction of Lasem as a heritage city. This program also opens up space for ongoing collaboration between local stakeholders in developing community-based cultural tourism in a more systematic and sustainable manner.